in Government Research, Recognition, and Replication - Sandford Borins (ash institute for democratic governance and inn, 2008)
The Innovations in American Government Program at the Kennedy School’s Ash Institute was set up in 1986 in response to widespread concerns about the dangers to democracy arising from citizen apathy and consequent loss of trust in government. Over the years, the institute also has sought to restore citizen confidence and trust in government through the Innovations in American Government Awards Program, which recognizes, celebrates, and replicates the best innovations in government. Since the program was launched, 400 outstanding government innovations have been recognized, and the institute has awarded in excess of $20 million to disseminate and replicate these innovative ideas. Perhaps it will not be an exaggeration to claim that the attempt to make government effective through innovation is fast becoming a worldwide movement toward effective good governance. The program has been widely replicated, with sister programs in Brazil, Chile, China, Kenya, Mexico, Peru, the Philippines, and South Africa, and awards programs such as this have emerged as a major tool for promoting government innovation. Nor can one deny the Innovations in American Government Program’s transformative impact on the way in which the public purpose is realized and governance delivered.